Strategi Pengambilan Keputusan Taktis dalam Akuntansi Manajemen untuk Meningkatkan Efisiensi UMKM: (Studi kasus pada Toko AIS Kamal) - Nadiatul Ayu Ananda; Fibriyanti Anjali; Santiayu Wulan Sari; Anggita Eka Syahrani Putri; Elina Zahrotul Firdaus; Mochamad Reza Adiyanto (Universitas 45 Surabaya, 2025)
This research abstract aims to analyze the problems faced by Micro, Small and Medium Enterprises (MSMEs) in making decisions related to management accounting. This research focuses on Toko AIS in Kamal, which experiences low operational efficiency due to inefficient cost management and lack of technology utilization. The method used is a qualitative approach with a case study, which allows researchers to explore in-depth information about managerial and financial practices. The results showed that intuition-based decision-making hindered the growth potential of the business, thus requiring management accounting-based tactical strategies to improve efficiency and profitability. The findings are expected to provide practical solutions for Indonesian UMKM facing similar challenges, and contribute to the sustainability of their businesses.